Linear analysis of concrete arch dams including dam?water?foundation rock interaction considering spatially varying ground motions. - Wang, Jin-Ting (Earthquake engineering & structural dynamics.)
The available substructure method and computer program for earthquake response analysis of arch dams, including the effects of dam?water?foundation rock interaction and recognizing the semi-unbounded size of the foundation rock and fluid domains, are extended to consider spatial variations in ground motions around the canyon. The response of Mauvoisin Dam in Switzerland to spatially varying ground motion recorded during a small earthquake is analyzed to illustrate the results from this analysis procedure.